Pengaruh Brand Image PT. Telekomunikasi Selular Terhadap Minat Beli Konsumen di Kota Pekanbaru - Aliyah, Rifdah; Primasari, Intan (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2023)
Telkomsel Orbit is an all-digital portable modem that is one of the latest superior products from PT. Cellular Telecommunications (Telkomsel). This modem allows users to access the internet anywhere and anytime because of its minimalist shape and easy to carry, the internet speed offered is up to 1 gbps and can connect to more than 30 devices. Brand image that has been built by PT. Cellular Telecommunications (Telkomsel) has an impact on the interest in buying this new product. This study has two variables with Brand Image (X) as the independent variable and Buying Interest (Y) as the dependent variable. With the aim to measure the influence of brand image on buying interest. The method used in this study is quantitative method with descriptive analysis. Sampling was carried out using the non-probability sampling method with respondents as many as 100 Telkomsel Orbit consumers domiciled in Pekanbaru City. Data analysis techniques use descriptive analysis and simple linear regression analysis. The results indicated that the brand image variable had a positive and significant effect on buying interest by 62.6%.